A Co-Printed Nanoslit Surface Plasmon Resonance Structure in Microfluidic Device for LMP-1 Detection - Shu-Cheng Lo; Shao-Sian Li; Wen-Fai Yang; Kuang-Chong Wu; Pei-Kuen Wei; Horn-Jiunn Sheen; Yu-Jui Fan (Biosensors, 2022)
This paper reports a novel micro/nanostructure co-hot embossing technique. Gold-capped nanostructures were used as localized surface plasmon resonance (SPR) sensors and were integrated into a microfluidic channel. The advantage of the co-hot embossing technique is that the SPR sensors do not need to be aligned with the microfluidic channel while bonding to it. The integrated SPR sensor and microfluidic channel were first characterized, and the sensitivity of the SPR sensor to the refractive index was found using different concentrations of glycerol solutions. The SPR sensor was also used to quantify latent membrane protein (LMP-1) when modifying anti-LMP-1 at the surface of the SPR sensor. Different concentrations of LMP-1 samples were used to build a calibration curve.